At the Crossroads: Lessons and Challenges in Computational Social Science - Javier Borge-Holthoefer (Frontiers Research Topics, 2016)
The interest of physicists in economic and social questions is not new: for over four decades, we have witnessed the emergence of what is called nowadays "sociophysics" and "econophysics", vigorous and challenging areas within the wider "Interdisciplinary Physics". With tools borrowed from Statistical Physics and Complexity, this new area of study have already made important contributions, which in turn have fostered the development of novel theoretical foundations in Social Science and Economics, via mathematical approaches, agent-based modelling and numerical simulations. From these foundations, Computational Social Science has grown to incorporate as well the empirical component -aided by the recent data deluge from the Web 2.0 and 3.0-, closing in this way the experiment-theory cycle in the best tradition of Physics.